The value of skill training programs for self-employment, entrepreneurship and non-cognitive traits. Evidence from a regression discontinuity design - Shubha Chakravarty; Mattias K. A. Lundberg; Plamen Nikolov; Juliane Zenker (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
Using a "fuzzy" regression discontinuity design, we examine the short-run impacts of a vocational training program on self-employment, new business plans, entry into entrepreneurship and entrepreneurial traits using data from the Nepal Employment Fund training program, which funds training workshops offered to eligible individuals. We find striking positive effects of training on self-employment among transformative entrepreneurs. Among individuals who our analysis identifies as transformative entrepreneurs, training provision increases the likelihood of self-employment by 0.21, or equivalent to a 50 percent increase in self-employment from the baseline average. We find impact differences by gender: self-employment increase by 21 percent among women and we detect no impacts among men. The program also generated sizable improvements in self-reported self-regulation and a decreased frequency of anxiety about future income. The female sub-sample and the most labor-intensive training types primarily drive the positive program impacts.
Keywords: J24; M53; L26; O15; 330; Regression Discontinuity Design; Human Capital; Labor Markets; Selfemployment; Entrepreneurship; Nepal